Modelo de exportación de café robusta hacia Colombia para las asociaciones campesinas del nor oriente ecuatoriano - Aguilar Zambrano, Mayra (2006)
The rural coffee sector of Ecuador’s North-East suffers of problems in the commercialization of its products. The Ecuadorian Corporation of Coffee – CORECAF - inside the execution of the Coffee Project Amaznor in the provinces of Orellana and Sucumbíos has considered the export like an alternative strategy to improve the conditions of its beneficiaries' commercialization. The present study, based on the in-formation provided by the CORECAF, interviews and socialization shops, has developed an export model adapted to the peculiar needs and conditions of the Rural Associations of Ecuador’s North-East (AGRODUP, APROCASH, AGROECOCAFÉ, APROCAS and APROCEL). The model indicates step by step the necessary docu-ments and the people would be the responsible of carrying out them inside the company. Likewise the study carried out the financial eval-uation that generated the approaches and necessary indicators to con-sider the viability of the export proposal. Finally it suggests that better conditions should exist so much operative, productive, organizational and of market that they contribute with a better scenario to implement the exporter strategy.